Ozaveščanje javnosti o paliativni oskrbi - Zelko, Erika (AS. Andragoška spoznanja, 2021)
aising awareness and educating the general public about palliative care can improve both palliative care itself and the last days of patients with incurable illnesses. This is also the purpose of the interna-tional programme Last Aid, which provides community training on palliative care and is carried out in 18 countries. It was first implemented in Slovenia in the second half of 2019 and 25 courses have been conducted thus far. 350 people have attended the course and 255 have completed and handed in the eval-uation questionnaires. The aim of the article is to present our analysis of the Last Aid course evaluation in Slovenia. Based on the analysis of the data obtained by the qualitative and quantitative method, we can conclude that the educational programme was well received by the Slovenian population as the participants were very satisfied with both the content and implementation of the course. The course received the highest grade (5) from 87.7% of the participants and individual modules were assessed with the highest grade by more than 75% of the participants. Overall, the participants mostly evaluated the interactivity of the course and the opportunity to share experiences as positive, however, the analysis also shows that the programme needs to be upgraded to include additional topics.
Keywords: education; general public; izobraževanje; Last Aid course; paliativna oskrba; palliative care; Slovenia; Slovenija; splošna javnost; tečaj Last Aid